Characterization of Diclofenac-induced Renal Damage in Normotensive and Hypertensive Rats: A Comparative Analysis - Boeing, Thaise; Lima, Alana Bittencourt F.; Busana, Maria Eduarda; Mariano, Luísa Nathália Bolda; da Silva, Luisa Mota; Silva, Rita de Cássia Vilhena da; de Souza, Priscila (Drug Research, 2024)
Background Diclofenac is the non-steroidal anti-inflammatory drug (NSAID) mostly prescribed worldwide, but it is highly associated with hypertension and acute kidney injury. Despite that, little information is available about the renal effects of diclofenac in hypertensive individuals, which led us to carry out this comparative study between the renal effects of this NSAID in normotensive (NTR) and spontaneously hypertensive rats (SHR).Methods Male Wistar NTR and SHR were orally treated with vehicle (V: 10 mL/kg) or diclofenac sodium (D: 100 mg/kg) once a day for 3 days. Urine volume, electrolytes excretion (Na+, K+, Cl-, and Ca2+), urea, creatinine, pH, and osmolarity were evaluated. Furthermore, blood samples and renal tissue were collected to perform biochemical and histological analysis.Results Diclofenac increased the renal corpuscle and bowman’s space in the SHR, while no microscopic changes were observed in the renal tissue of NTR. Regarding the urinary parameters, diclofenac reduced urine volume, pH, osmolarity, and all electrolytes excretion, followed by decreased urea and creatinine levels in both lineages. Moreover, it also induced hyponatremia, hypokalemia, and hypocalcemia in SHR, while reduced glutathione-S-transferase activity, lipid hydroperoxides, and nitrite levels in renal tissue.Conclusions The data presented herein demonstrated that diclofenac induces renal damage and impaired renal function in both NTR and SHR, but those effects are exacerbated in SHR, as seen by the histological changes and electrolytes balance disturbance, therefore, reinforcing that diclofenac may increase the risks of cardiovascular events in hypertensive patients.
Keywords: diclofenac sodium; kidney; renal corpuscle; hypertension; diuresis